Assessment and mitigation of university student's mental health during COVID-19 / Hasanathul Bashariyah Kamaludeen - Hasanathul Bashariyah, Kamaludeen (2021)
In higher education, student mental health has become a growing problem. The COVID-19 pandemic has refocused attention on this vulnerable group. This study seeks to provide a comprehensive assessment of the impact of the COVID-19 pandemic on university student’s mental health. To assess the mental health status of public university students in Malaysia, an online survey using GAD-7 and PHQ-9 screening tests was conducted with 200 students and the data was analyzed through quantitative methods. The mental health statistical analysis using IBM Statistical Product and Service Solutions (SPSS) version 27.0 revealed that the 88 students (44.00%) were highly experiencing mild anxiety symptoms. Whereas, 74 students (37.00%) were highly experiencing mild depressive symptoms during this COVID-19 outbreak. However, significant findings reported that 25 students (12.50%) and 24 students (12.00%) have severe anxiety and depressive symptoms respectively. The level of anxiety, depression of the students and the duration of the students staying alone or away from the family has a significant correlation with each other of at least r=0.147. These findings have encouraged the researcher to propose a mitigation model for universities to address mental health issues among university students.